The Effect of Self-Confidence and Emotional Intelligence on Leadership Effectiveness - Ani, Fitri; Chansa Thelma, Chanda (JUMPA : Jurnal Manajemen Pendidikan, 2023)
This study aims to explore the influence of self-confidence and emotional intelligence on leadership effectiveness, with a particular focus on Madrasah Aliyah Miftahul Ulum.  The research method used is a quantitative approach with survey design. The research sample consisted of leaders at MA Miftahul Ulum. The instruments used include questionnaires to measure levels of confidence and emotional intelligence, as well as surveys to assess leadership effectiveness from the perspective of subordinates. Data analysis was performed using linear regression to determine the relationship between self-confidence, emotional intelligence, and leadership effectiveness. The findings showed that self-confidence and emotional intelligence had a significant positive correlation with leadership effectiveness. Leaders who have high levels of self-confidence tend to be better able to make bold and informed decisions, while high emotional intelligence helps them understand and manage the emotions of themselves and their subordinates. The results of this study are relevant in the context of the leadership of the principal at MA Miftahul Ulum. Leaders with high confidence can make more strategic decisions in developing educational programs. In addition, high emotional intelligence helps leaders in creating a harmonious and supportive learning environment. The implications of this study suggest that leadership development programs at MA Miftahul Ulum should include training to improve leaders' confidence and emotional intelligence. This can help improve leadership effectiveness and overall educational performance.